Modeling substance use in emerging adult gay, bisexual, and other YMSM across time: The P18 cohort study - Halkitis, Perry N. (Drug Alcohol Depend, 2014)
OBJECTIVE: To examine patterns of substance use over time in a new generation of emerging adult gay, bisexual, and other young men who have sex with men (YMSM). METHODS: Data were drawn from the first four waves of on ongoing prospective cohort study of YMSM who were ages 18 to19 at baseline and were assessed each 6 months for substance use via calendar based methods. Latent growth curve modeling was utilized to assess changes over time for four drug use categories: alcohol, marijuana, inhalant nitrates, and other drugs (e.g., cocaine, ecstasy) and between groups (race/ethnicity, perceived familial socioeconomic status; SES). RESULTS: Use of all substances increased steadily across the follow-up period. White YMSM demonstrated higher levels of alcohol use at the 18-mo follow-up visit compared to other racial/ethnic groups, while rates of change across groups were similar. Marijuana use at 18 months was highest for Hispanics who also indicated the highest rate of change. Finally, YMSM who reported higher perceived SES reported the lowest use and lowest rates of change for other drug use. Controlling for perceived SES, differences in patterns of drug use by race/ethnicity were evident but differences were not as large. CONCLUSIONS: Increases in substance use in the emerging adulthood of YMSM indicate the need for structural and behavioral interventions tailored to address substance use in these young men before chronic patterns of use develop. Differences in patterns of drug use across racial/ethnic and SES groups suggest that interventions need to consider person-level differences.